ADAPTIVE DA'WAH STRATEGY IN INCREASING CONGREGATION PARTICIPATION IN ROUTINE STUDIES AT THE ISLAMIC STUDY ASSEMBLY DARUSSHOFA MEDAN - Hanifah, Aqimah Al; Tanjung, Muaz (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyze the da'wah strategies implemented by the Majelis Taklim Darusshofa Medan to increase congregational participation in routine religious study activities. The study used a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, participant observation, and documentation studies involving administrators, preachers, and congregational members. Data were analyzed using thematic analysis techniques to identify key patterns and themes. Using descriptive qualitative methods, data collection was carried out through participatory observation, documentation studies, and in-depth interviews with 15 informants consisting of assembly administrators, preachers, and active and passive congregations in order to obtain a comprehensive perspective. The results indicate that effective da'wah strategies include personal and community approaches, innovative study programs, and the use of digital technology as a means of disseminating information. These strategies contribute to increased awareness, motivation, and sustained congregational participation in routine religious study activities. This study emphasizes the importance of adaptive da'wah practices oriented to community needs in strengthening religious engagement within the majelis taklim environment. The success of increasing congregational participation was driven by the integration of contextual da'wah strategies that combine a bil-hikmah (persuasive) approach with the use of digital media as a means of dissemination and coordination. These findings provide practical contributions for da'wah institution managers in mapping the needs of urban congregations, while also providing theoretical insights into the effectiveness of persuasive communication in strengthening socio-religious cohesion in urban environments.